Syrian Newcomer Students Share Their Experiences in Canadian Schools - Mohamad Ayoub; George Zhou (Brock University, 2023)
The purpose of this study was to investigate the experiences of Syrian refugee students in Canadian schools. Article 12 of the Convention on the Rights of the Child (CRC) was used as a framework. Data collection involved one-on-one interview with students. Data from the interviews was analyzed using an open-coding technique to identify themes and patterns. Although the students had positive resettlement experiences, some of them experienced difficulties with their learning. Based on the findings, we propose recommendations for educators and schools welcoming Syrian refugee students.